The Moment of Study in Learning that Resists Neoliberalism: Body Gesture, Time, and Play - Joldersma, Clarence (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
The essay develops a case study about a young boy playing with a toy train to address neoliberalism’s problematic discourse that depicts learning as instrumental, as something that can be caused by teaching. This paper’s perspective is enactive, taking the view that central to understanding learning is not the mind or brain working in isolation but involves the interrelationships between mind/brain, body, and world. The analysis revolves around the standing gap between teaching and learning, where navigating the gap involves a dynamic called ‘the moment of study.’ Three of Tyson Lewis’s ideas about study—body gesture, time, and play—are used to explain the moment of study. The paper argues that a learner traverses the gap between teaching and learning through a body gesture of hesitation, during which there is a temporal turning away from the familiar and towards new possibilities. Traversing the gap occurs through the risk of improvisational play, propelling a forward movement in the face of not knowing how to go on. This depiction of such traversing, shown to be central to the activity of learning, undermines the causal account of learning associated with neoliberalism.